Diet-induced obesity and aging-induced upregulation of Trib3 interfere with energy homeostasis by downregulating the thermogenic capacity of BAT - Hyejin Yeo; Ji-Hye Lim; Ji Eom; MinJeong Kim; Hyeji Kwon; Sang-Wook Kang; Youngsup Song (Experimental and Molecular Medicine)
Abstract Characterized by UCP1 expression and abundant mitochondria, brown adipose tissue (BAT) plays a crucial role in energy balance by converting chemical energy into heat through the cost of ATP production. In this study, it was demonstrated that Trib3 is a critical determinant of BAT-mediated energy expenditure and whole-body energy homeostasis. Under 60% high-fat diet conditions, Trib3 expression in BAT was elevated. Mice deficient in Trib3 are resistant to diet-induced obesity and exhibit improved glucose homeostasis due to enhanced BAT activity. Furthermore, brown adipocyte progenitor cells (APCs) lacking Trib3 exhibited increased proliferation and promoted brown adipocyte differentiation and mitochondrial biogenesis, contributing to the increase in the maximal thermogenic capacity of BAT in Trib3-deficient mice. Mechanistically, it was discovered that Trib3 expression is upregulated by free fatty acids at the transcriptional level and synergistically upregulated by DAG-PKC at the posttranslational level. This occurs through the modulation of COP1-mediated Trib3 protein turnover. Interestingly, the level of Trib3 expression in BAT increased with age. Trib3 knockout mice were protected from aging-related weight gain and impaired glucose homeostasis. These results suggest that Trib3 acts as an obesity- and aging-associated factor that negatively regulates BAT activity and that the loss of Trib3 may provide a beneficial approach to prevent obesity and aging-associated metabolic syndrome by increasing the thermogenic capacity of BAT.